2005
DOI: 10.1021/la052539m
|View full text |Cite
|
Sign up to set email alerts
|

Solution-Phase Synthesis of Spherical Zinc Sulfide Nanostructures

Abstract: A facile solution-phase method has been developed to synthesize specially hollow and solid ZnS nanospheres. High-resolution TEM images on the nanospheres suggest their formation via the oriented aggregation of the primary ZnS nanocrystals. The morphology and size of the ZnS nanospheres can also be tuned easily by controlling the experimental conditions. These special spherical structures are very easily encapsulated within a uniform silica layer without any surface modification, suggesting potential applicatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

5
40
0

Year Published

2007
2007
2015
2015

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 77 publications
(45 citation statements)
references
References 50 publications
(21 reference statements)
5
40
0
Order By: Relevance
“…SEM images revealed (Fig. 2) the rough surface of these microspheres that are composed of several smaller particles with an average diameter of the order of nm when observed at higher resolution in accordance with the reported results of ZnS microstructures [22,23]. Fig.…”
Section: Sem Analysissupporting
confidence: 87%
“…SEM images revealed (Fig. 2) the rough surface of these microspheres that are composed of several smaller particles with an average diameter of the order of nm when observed at higher resolution in accordance with the reported results of ZnS microstructures [22,23]. Fig.…”
Section: Sem Analysissupporting
confidence: 87%
“…Absorption bands at 462 (Si-O-Si band), 798 (Si-O-Si symmetric strength), and 1083 cm 21 (Si-O-Si antisymmetric strengths) were observed after SiO 2 coating. 20,21 The data suggested strongly that the iron-carbon composite particles were really encapsulated within the silica matrix. The BET surface area of silica-coated iron-carbon composite particles was estimated to be 264.16 m 2 /g, which is considerably large since the Fe particles have been included in the calculation.…”
Section: Resultsmentioning
confidence: 97%
“…Some groups [22][23][24] have reported that hollow CaCO 3 , CoOOH and ZnS could be successfully prepared by using CO 2 , O 2 and H 2 S bubble as soft templates. Under the conditions of our experiments, the following reactions are thought to be occurred in the process of porous hollow ZnO…”
Section: Resultsmentioning
confidence: 99%